AL-NISWIYAH FI RIWAYAH NAWAL AL-SA’DAWI "IMRA'AT ‘INDA NUQTAH AS-SHIFR" - Miftahul Ilmia; Abdul Wahab Naf'an (Journal of Arabic Literature (JaLi), 2023)
This study describes the form of movement and resistance of the main female character in Nawal El Saadawi's novel Imra'at 'inda nuqtah as-shifr against the oppression of a patriarchal society. The aims of this study are to 1) Define the portrayal of the heroine in the novel imra'at 'inda nuqtah as-shifr. 2) Define the form of female resistance in the post-colonial period. 3) Analyze the form of expression of women's rights in Nawal El Saadawi's imra'at 'inda nuqtah as-shifr from the perspective of Anya Loomba. This study uses a descriptive qualitative research approach to analyze the actions and resistance of the female protagonist portrayed through the narrative. The data in this study are in the form of quotes describing women's resistance to the patriarchal cultures they encounter. The findings of this study are: 1) The protagonist, Firdaus, is portrayed as a woman who suffers from acts of injustice in the patriarchal culture. Firdaus is described as a strong woman in the face of her difficult life. 2) Firdaus' actions reflect the female resistance that the main character undertakes to protect herself. 3) The expression of women's rights in imra'at 'inda nuqtah as-shifr in the post-colonial period depicts courageous women demanding the rights they deserve, such as education, work, and success. Women can express their rights among patriarchal races.